The kinematics of very low mass dwarfs: Splinter session summary. Issue 1 (6th February 2013) - Burgasser, A.J.; Faherty, J.K.; Schmidt, S.; West, A.A.; Zapatero Osorio, M.R.; Pineda, J.S.; Burningham, B.; Nicholls, C.; Sanderson, R.; Shkolnik, E.; Rodriguez, D.; Riedel, A.; et al.
Abstract Kinematic investigations are being increasingly deployed in studies of the lowest mass stars and brown dwarfs to investigate their origins, characterize their atmospheres, and examine the evolution of their physical parameters. This article summarizes the contributions made at the "Kinematics of Very Low Mass Dwarfs" splinter session. Results discussed include analysis of kinematic distributions of M, L, and T dwarfs; theoretical tools for interpreting these distributions; identifications of very low mass halo dwarfs and wide companions to nearby stars; radial velocity variability among young and very cool brown dwarfs; and the search and identification of M dwarfs in young moving groups. A summary of discussion points at the conclusion of the splinter sesseion is also presented. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)